Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Materi Persamaan Kuadrat Berdasarkan Prosedur Newman - Desyane Natalia Mekar Pania; Vivian E. Regar; Rosiah J. Pulukadang (Journal on Education, 2023)
This study aims to determine errors and factors that cause students to make mistakes in solving word problems on quadratic equations based on the Newman procedure. The type of research used is descriptive research. Data collection techniques used were written tests, interviews and documentation. The research subjects were 20 students of class IXA at SMP Kristen Tomohon. The results showed that in solving word problems on the quadratic equation material given by the students they still made mistakes based on the Newman procedure. Factors causing students to make mistakes, namely: misreading the numbers in the problem, confused with the formula that students will use in a hurry to solve the problem so they don't write down the final answer. Based on the results of this study, it is suggested to mathematics teachers to provide story questions to students by applying Newman's procedure so that the answers given are more structured.